2014
DOI: 10.1021/om500570d
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecularly Sulfur-Stabilized Silicon Cations as Lewis Acid Catalysts

Abstract: The synthesis and spectroscopic characterization of previously unprecedented sulfur-stabilized silicon cations are reported. Several 1,3-dithiolan-2-yl- and 1,3-dithian-2-yl-substituted silanes were prepared and successfully transformed into the corresponding silicon cations by hydride abstraction. The silicon–sulfur interaction creates three consecutive stereocenters at three different elements. It is remarkable that the present stereocenter at the silicon atom determines the stereochemical outcome at the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 73 publications
1
60
1
1
Order By: Relevance
“…8, 9 As part of our ongoing research, we recently reported the synthesis of intramolecularly sulfur-stabilized silicon cation 6 with a planar chiral ferrocenyl substituent (Figure 2, left). 10 Its ability to act as a Lewis acid catalyst was demonstrated in the difficult Diels−Alder reaction of cyclohexa-1,3-diene and chalcone, but no asymmetric induction was seen.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8, 9 As part of our ongoing research, we recently reported the synthesis of intramolecularly sulfur-stabilized silicon cation 6 with a planar chiral ferrocenyl substituent (Figure 2, left). 10 Its ability to act as a Lewis acid catalyst was demonstrated in the difficult Diels−Alder reaction of cyclohexa-1,3-diene and chalcone, but no asymmetric induction was seen.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Inspired by cation 5 (Figure 1, bottom right), we also targeted the axially chiral dihydrosilepine (S)-10 with a 2-[(alkylthio)methyl]phenyl group installed at the silicon atom (Figure 3, bottom). Different from our previous work, 10 we aimed to accomplish stabilization by acyclic rather than cyclic dialkyl thioethers (cf. 1,3-dithiolan-2-yl and 1,3-dithian-2-yl substituents in 6 and 7a− 7d, respectively, Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic methodologies to prepare the ferrocenyl-functionalized β-diketones 5 – 8 is shown in Scheme 1 . The therefore necessary starting compounds 1 – 3 were synthesized accordingly to references [ 79 , 80 , 81 ]. Ketone 4 was prepared by a Friedel-Crafts acylation of ferrocene with 2-[2-(2-methyoxyethoxy)ethoxy]acetyl chloride, which is accessible by refluxing the appropriate carboxylic acid with thionyl chloride in analogy to references [ 82 , 83 ], with ferrocene in presence of the Lewis acid catalyst AlCl 3 ( Section 4.6 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, most isolable silylium ions are typically limited to alkyl and aryl substituents and heteroatom-substituted silylium derivatives have remained extremely scarce. However, introduction of a heteroatom such as N, O, or S to the silylium center [20][21][22] produced silylium ions with good catalytic activity [23].…”
Section: Introductionmentioning
confidence: 99%